KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PADA SMP ISLAM TERPADU AL-FITYAN KABUPATEN ACEH BESAR - Zulkarnaen Jafar, Yusrizal, Khairuddin (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
ABSTRACT: Managerial Competence is the skill of principals to improve the performance of teachers in implementing the learning process at schools. The purpose this study was to investigate the program, implementation, and monitoring of teacher performance improvement. This study used a qualitative approach with descriptive methods, and the techniques of data collection done were observation, interviews, and documentation. The subject of this study was the principal, vice-principal, and teachers of Integrated Islamic Junior High School of Al-Fityan. The results showed that 1) The programs made by the principal in improving the performance of teachers at Integrated Islamic Junior High School of Al-Fityan were teacher training, educational seminars, teacher workshop, Teacher Professional development Networks (MGMPs), Teacher Working Group (KKG), awards to teachers who excel and also adds incentive for teachers as well as to provide an opportunity for teachers to use IT tools in learning; 2) the implementation of the program to improve the performance of teachers at Integrated Islamic Junior High School of Al-Fityan was by engaging teachers through teacher training programs, educational seminars, workshop teacher, MGMPs, KKGs, giving awards to teachers who excel and also adding incentives teacher as well as providing an opportunity for teachers to use IT tools in learning; 3) Monitoring done principal in improving teacher performance at Integrated Islamic Junior High School of Al-Fityan was carried out continuously and sustainably through two-way communication with teachers, as well as classroom visits with notice and without notice, individual communication, and by inviting inspectors to the school to evaluate the performance improvement program and receiving input and direction.KEYWORDS: managerial competence, principal, and teacher performance ABSTRAK: Kompetensi Manajerial merupakan keterampilan kepala sekolah untuk meningkatkan kinerja guru dalam melaksanakan kegiatan belajar mengajar di sekolah. Penelitian ini bertujuan untuk mengetahui program peningkatan kinerja guru, pelaksanaan program peningkatan kinerja guru, dan Pengawasan program peningkatan kinerja guru. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, sedangkan teknik pengumpulan data dilakukan melalui observasi, wawancara, dan studi dokumentasi. Adapun subjek penelitian ini adalah kepala sekolah, wakil kepala sekolah, dan guru SMP Islam Terpadu Al-Fityan. Hasil penelitian menunjukkan bahwa 1) Program kepala sekolah dalam meningkatkan kinerja guru di SMP Islam Terpadu Al-Fityan adalah dengan program pelatihan guru, seminar pendidikan, workshop guru, MGMP, KKG, memberi penghargaan kepada guru yang berprestasi dan juga menambah insentif guru serta memberi kesempatan kepada guru untuk menggunakan perangkat IT dalam pembelajaran, 2) Pelaksanaan program peningkatan kinerja guru di SMP Islam Terpadu adalah dengan mengikutsertakan guru melalui program pelatihan guru, seminar pendidikan, workshop guru, MGMP, KKG, memberi penghargaan kepada guru yang berprestasi dan juga menambah insentif guru serta memberi kesempatan kepada guru untuk menggunakan perangkat IT dalam pembelajaran, 3) Pengawasan kepala sekolah dalam meningkatkan kinerja guru SMP-IT Al-Fityan dilakukan secara terus-menerus dan berkesinambungan melalui komunikasi dua arah dengan guru, serta kunjungan kelas dengan pemberitahuan dan juga tanpa pemberitahuan, komunikasi secara individu, dan mengundang pengawas ke sekolah untuk mengevaluasi program peningkatan kinerja guru sekolah serta menerima masukan dan arahanKATA KUNCI: kompetensi manajerial, kepala sekolah dan kinerja guru